Patterns of Children’s Relationships With Parents and Teachers in Grade 1: Links to Task Persistence and Performance - Silinskas, Gintautas; Kikas, Eve (Frontiers in Psychology, 2022)
Our study aimed to investigate the patterns of children’s relationships with their parents and teachers, the development of these relationships during Grade 1, and respective links to children’s learning (in task persistence and performance). Parents of 350 children answered questionnaires about the quality of their relationships with their children; 25 teachers answered questions about children’s task persistence at school and the quality of their relationships with their students; 350 children completed literacy and math performance tests; and six testers evaluated children’s task persistence when completing those tests. All measures were administered twice: at the start and end of Grade 1. Latent profile analyses found two meaningful child profiles that were similar at the beginning and end of Grade 1: average relationship (89% at T1, 85% at T2) and conflictual relationship (11% at T1, 15% at T2) with parents and teachers. These profiles were highly stable throughout Grade 1, except for 15 children who moved from an average relationship to a conflictual relationship profile. This declining trajectory can be characterized by poor relationships with teachers and low task persistence at the end of Grade 1, although they did not perform any worse than other children. Finally, children exhibiting conflictual relationships with their parents and teachers at the beginning of Grade 1 performed worse on spelling and subtraction tasks and demonstrated lower task-persistent behavior at the end of Grade 1 than those with average (good) relationships with parents and teachers.